1986
DOI: 10.1111/j.1365-4362.1986.tb04534.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing 2.5%, 5%, and 10% Benzoyl Peroxide on Inflammatory Acne Vulgaris

Abstract: A 2.5% formulation of benzoyl peroxide was compared with its vehicle, and with a 5% and a 10% proprietary benzoyl peroxide gel preparation in three double-blind studies involving 153 patients with mild to moderately severe acne vulgaris. The 2.5% benzoyl peroxide formulation was more effective than its vehicle and equivalent to the 5% and 10% concentrations in reducing the number of inflammatory lesions (papules and pustules). Desquamation, erythema, and symptoms of burning with the 2.5% gel were less frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 6 publications
2
59
0
4
Order By: Relevance
“…Similar age distribution and female preponderance was seen in a study done by Rallis E et al 10 Group I treated with 5% Benzoyl peroxide were followed up at 2 weeks and 4 weeks which showed 32.3% and 58.03% percentage reduction of number of lesions respectively. This data correlates with the study conducted by Mills OH et al, in 1986, who demonstrated 40.3% and 55.9% percentage of reduction in acne lesions from baseline at the end of 4 weeks and 8 weeks respectively which is in concordance with our study.…”
Section: Discussionsupporting
confidence: 93%
“…Similar age distribution and female preponderance was seen in a study done by Rallis E et al 10 Group I treated with 5% Benzoyl peroxide were followed up at 2 weeks and 4 weeks which showed 32.3% and 58.03% percentage reduction of number of lesions respectively. This data correlates with the study conducted by Mills OH et al, in 1986, who demonstrated 40.3% and 55.9% percentage of reduction in acne lesions from baseline at the end of 4 weeks and 8 weeks respectively which is in concordance with our study.…”
Section: Discussionsupporting
confidence: 93%
“…In two trials of 153 patients with mild to moderate acne, Milis et al (57) compared the efficacy of topical benzoyl peroxide at different concentrations (2.5% vs. 5% and 2.5% vs. 10% used twice daily). Based on lesion counts, there were no differences in efficacy among the different concentrations.…”
Section: Tazarotenementioning
confidence: 99%
“…In a comparison of 2.5, 5 and 10% gel formulations of benzoyl peroxide, the 2.5% formulation was equivalent to the other two concentrations in reducing inflammatory lesions and significantly reduced P. acnes after 2 weeks of topical application. The local adverse effects were less frequent with the 2.5% gel than with the 10% preparation, but similar to the 5% gel [57]. …”
Section: Benzoylperoxidementioning
confidence: 99%